AB1247 Impact of a self-care education program for patients with osteoarthritis. (12th June 2018) - Gurt, A.; Llorente, J.; López, M.; Tio, L.; Sena, B.; Montañes, F.; Marco, E.; Verges, J.; Herrero, M.; Monfort, J.
Abstract : Background: Osteoarthritis (OA) has a prevalence rate that reaches 29% in people older than 60 years 1 . Treatments available are limited. The costs of OA in Spain are about 4.800 million euros/year 2 . Objectives: To create a self-care program for OA patients in order to improve their quality of life (QoL) and therefore to reduce the socioeconomic cost. Methods: The design of the program was carried out by 2 PC physicians, 1 rheumatologist, 1 rehabilitator, 1 nurse and 2 psychologists. The program included a total of 9 sessions of 1.5 hours once a week. There were 2 sessions for each of the following topics: general information, physical activity, nutrition, coping with the disease, and 1 summary session. Three OA patients were trained and afterwards they were in charge of imparting the program to other patients with the assistance of a nurse. Before and after the program some data was collected relating the patients' knowledge, food and physical activity habits, social networks and hours of rest. They were asked to complete WOMAC, EuroQol-5D, and HAD Scale questionnaires. The statistical analysis was performed using package SPSS v16. Results: 60 Knee OA patients were recruited from Hospital del Mar and Vila Olímpica PC centre, and divided into 6 different groups. Only the results of the first two groups are shown. Group1 (11 patients) and 2 (10 patients). First we analysed differences between the basal data and the ones collected after the last session. The analysis of the data from all the patients (groups 1 and 2) showed that in knowledge about OA management the average value obtained in the basal visit was 6.31±2.798, and 7.81±1.94 after the last session (p=0.024). Analysis of pain by VAS showed that the average value in the basal visit was 3.91±1.82, and 2.44±2.03 after the last session (p=0.014). We observe a tendency, although it doesn't reach significant differences in QoL, where the average value in the basal visit was 2.31±1.81, and 1.63±1.54 after the last session (p=0.052). In the HADS scale the average value in the basal visit was 9.86±6.02, and 8.36±5.40 after the last session (p=0.052). Regarding the analysis of differences between two groups, categorical items were analysed. In the total questionnaire at the end of the sessions the average for group 1 was 6.89 and for group 2 was 8.75 (p=0.038). Meeting with friends frequency at the beginning and at the end of the study was also different among groups (p=0.014/p=0.019). Conclusions: This self-care education program had a positive effect on the OA patients pain perception, and it could also be observed an improvement in QoL and the anxiety and depression. As differences among groups were also observed, socioeconomic and education aspects must be considered in the future. References: [1] Fernandez-Lopez JC, et al. EPISER StudyGroup. Prevalence, risk factors, and impact of knee pain suggesting osteoarthritis in Spain. Clin Exp Rheumatol. 2008;26(2):324–32. [2] Loza E, Lopez-Gomez JM, et al. Economic burden of knee and hip osteoarthritis in Spain. Arthritis Rheum. 2009 15;61(2):158–65. Disclosure of Interest: None declared